2005
DOI: 10.1137/040613706
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Passive Energy Transfer in Coupled Oscillators with Essential Nonlinearity

Abstract: Abstract. We study numerically and analytically the dynamics of passive energy transfer from a damped linear oscillator to an essentially nonlinear end attachment. This transfer is caused by either fundamental or subharmonic resonance capture, and in some cases is initiated by nonlinear beat phenomena. It is shown that, due to the essential nonlinearity, the end attachment is capable of passively absorbing broadband energy at both high and low frequencies, acting, in essence, as a passive broadband boundary co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
139
0
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(148 citation statements)
references
References 18 publications
3
139
0
6
Order By: Relevance
“…Firstly, it cannot be easily extended to nonconservative systems. However, as discussed in the companion paper, Part I, and in [15,26], the damped dynamics can often be interpreted based on the topological structure of the NNMs of the underlying conservative system. Moreover, due to the lack of knowledge of damping mechanisms, engineering design in industry is often based on the conservative system, and this even for linear vibrating structures.…”
Section: Framework and Definitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, it cannot be easily extended to nonconservative systems. However, as discussed in the companion paper, Part I, and in [15,26], the damped dynamics can often be interpreted based on the topological structure of the NNMs of the underlying conservative system. Moreover, due to the lack of knowledge of damping mechanisms, engineering design in industry is often based on the conservative system, and this even for linear vibrating structures.…”
Section: Framework and Definitionsmentioning
confidence: 99%
“…The dynamics of such systems have been extensively studied by Vakakis and co-workers [15,26,35,36] using the NNM concept. The motivation for using an essential nonlinearity is that the nonlinear attachment possesses no preferential resonant frequency; it can, therefore, interact with an SDOF structure in a frequency-independent fashion or with any mode of an MDOF structure.…”
Section: Strongly Nonlinear 2dof Systemmentioning
confidence: 99%
“…The following simulations were performed for shock excitation (5) The dynamical mechanisms governing passive targeted energy transfer from linear to nonlinear oscillators are discussed in previous works [5,6]. Two of these mechanisms rely on resonance capture of the damped dynamics on either fundamental or subharmonic resonant manifolds in the phase space of the dynamical system; viewed from an alternative perspective, irreversible targeted energy transfer from the linear oscillator to the nonlinear attachment takes place when the dynamics is restricted to a damped nonlinear normal mode invariant manifold, whose mode shape becomes strongly localized to the nonlinear attachment as the energy deceases due to damping dissipation.…”
Section: Optimization Of Passive Energy Transfer and Dissipation At Tmentioning
confidence: 99%
“…In particular, it was shown that transient resonance captures of the transient dynamics in neighborhoods of resonance manifolds of the phase space of a dynamical system [3,4] may initiate one-way, irreversible targeted energy transfer from a linear (main) subsystem to a local essentially nonlinear attachment, which acts, in essence, as nonlinear energy sink (NES) [5,6]. Moreover, in contract to the classical linear vibration absorber, the NES may passively absorb broadband energy over wide frequency ranges; this due to the essential stiffness nonlinearity of the NES, which enables resonance capture of the NES with any mode of the linear subsystem, irrespective of its frequency.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it was shown that an NES, i.e., an essentially nonlinear absorber, can extract energy from virtually any mode of a host structure [8]. The NES can also carry out targeted energy transfer, which is an irreversible channeling of vibrational energy from the host structure to the absorber [9]. This makes nonlinear vibration absorbers suitable candidates for vibration mitigation of nonlinear primary structures.…”
Section: Introductionmentioning
confidence: 99%